1997
DOI: 10.1002/(sici)1520-6327(1997)34:3<313::aid-arch6>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Activity of insulin growth factors and shrimp neurosecretory organ extracts on a lepidopteran cell line

Abstract: Ecdysteroids, or molting hormones, have been proven to be key differentiation regulators for epidermal cells in the postembryonic development of arthropods. Regulators of cell proliferation, however, remain largely unknown. To date, no diffusible insect peptidic growth factors have been characterized. Molecules structurally related to insulin have been discovered in insects, as in other eucaryotes. We developed in vitro tests for the preliminary characterization of potential growth factors in arthropods by ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The growth-promoting activity of insulin and insulin-like growth factors has been amply documented in both vertebrate cells and organ cultures. In insect cell cultures, exogenous insulin and insulin-like growth factors provoke physiological effects (Seecof and Dewhurst, 1974;Davis and Shearn, 1977;Martin and Shearn, 1980;Mosna, 1981;Wyss, 1982;Cullen and Milner, 1991;Hatt et al, 1994Hatt et al, , 1997 and mammalian insulin is presently a routine additive to Drosophila culture media (Wyss, 1988;Echalier, 1997). Nijhout and Grunert (2002) reported that bombyxin-II stimulates cell division and growth of wing imaginal disks of Precis coenia.…”
Section: Discussionmentioning
confidence: 99%
“…The growth-promoting activity of insulin and insulin-like growth factors has been amply documented in both vertebrate cells and organ cultures. In insect cell cultures, exogenous insulin and insulin-like growth factors provoke physiological effects (Seecof and Dewhurst, 1974;Davis and Shearn, 1977;Martin and Shearn, 1980;Mosna, 1981;Wyss, 1982;Cullen and Milner, 1991;Hatt et al, 1994Hatt et al, , 1997 and mammalian insulin is presently a routine additive to Drosophila culture media (Wyss, 1988;Echalier, 1997). Nijhout and Grunert (2002) reported that bombyxin-II stimulates cell division and growth of wing imaginal disks of Precis coenia.…”
Section: Discussionmentioning
confidence: 99%
“…Bhakthan & Gilbert 1968, Vanhems et al 1990, Hatt et al 1997, emphasizing some of the pleiotropic functions played by ILPs in animals. More particularly, investigations on the mosquito A. aegypti (Graf et al 1997, Riehle & Brown 1999 revealed ovarian steroidogenesis as a remarkable target of insulin in insects.…”
Section: The Physiological Significance Of the Ovarian Response To Inmentioning
confidence: 99%
“…Our knowledge of the insulin/mTOR pathway in crustaceans and its role in development and growth is fragmentary at best. Insulin-like peptides have been isolated from crustacean tissues (Gallardo et al, 2003;Hatt et al, 1997) and the androgenic gland expresses an insulin-like growth factor that determines male development (Banzai et al, 2011;Manor et al, 2007;Rosen et al, 2010;Sroyraya et al, 2010;. Insulin receptor tyrosine kinases and phosphotyrosyl phosphatases are present in crustacean tissues Chuang and Wang, 1994;Kucharski et al, 1999;Kucharski et al, 2002;Lin et al, 1993).…”
mentioning
confidence: 99%